마이크로웨이브를 이용한 금정광 내 금 용출 효율 증가 기작 - 김봉주(Bong-Ju Kim); 권장순(Jang-Soon Kwon); 고용권(Yong-Kwon Koh); 박천영(Cheon-Young Park) (자원환경지질, 2020)
In this research, we investigate the effect of microwave pretreatment on the recovery of gold from the gold concentrates by thiourea leaching. The changes in mineral phases by decomposition of pyrites in the gold concentrates using microwave were observed, and the result of microwave irradiation showed that the temperature of the irradiated sample increases with increasing irradiation time. With the reaction of temperature increases, Sulfur (S) in pyrites was converted to sulfur dioxide (SO2), and then the content of S in the sample was reduced. The analytical results of XRD and SEM-EDS showed that pyrites are converted to magnetite and hematite, and its surfaces are changed to a porous shape where micro-cracks are developed. The Au leaching efficiency from the irradiated gold concentrates using thiourea-mixed solvent increased with the increases of irradiation time and solvent concentration. The experimental results considering leaching parameters indicate that the mechanism of microwave irradiation increases the maximum leaching efficiency and leaching rate of the gold concentrates, and the solvent does a role for the increasing of leaching rate constant. 본 연구에서는 금정광내 금회수율을 증진하고자 마이크로웨이브 전처리방법을 이용하여 티오요소용출 실험을 수행하였다. 이에 본 연구에서는 먼저 마이크로웨이브를 이용하여 금정광 시료 내 황철석의 분해에 따른 광물상 변화를 관찰하였다. 마이크로웨이브의 조사시간이 증가함에 따라 시료의 온도는 증가하였고, 황철석 내 S가 SO2로 변환되어 시료 내 S의 함량이 감소되었다. X-선 회절분석 및 주사전자현미경 에너지 분산 분광분석을 통해 황철석은 자류철석과 적철석으로 변환되었으며, 미세균열이 발달된 다공질의 형태로 변질되었음을 확인할 수 있었다. 다양한 조건의 티오요소 혼합 용매를 이용하여 시료의 광물상변화에 따른 금 용출효율을 측정한 결과, 마이크로웨이브 조사시간 증가 및 용출실험 조건 내 용매의 농도 증가에 따라 용출효율이 증가하였다. 결론적으로, 마이크로웨이브를 활용한 금정광 조사는 시료 내 금의 최대용출효율과 용출속도를 증가시켰으며, 티오요소 용매제는 용출속도상수를 증가시켜주는 역할을 하였다.